التمكين الإداري وعلاقته بالأداء الوظيفي دراسة ميدانية بمؤسسة اتصالات الجزائر فرع سوق أهراس - زواهي ذكرى فريدة; صوالحية شيماء (My University, 2022)
Summary of the study: This study aims to analyze the relationship between administrative empowerment and job performance among workers in the Algerian company, Algeria Telecom, in the state of Souk Ahras. The following main question: What is the nature of the relationship between administrative empowerment and job performance? In order to test this and using the descriptive approach, we conducted a comprehensive survey of all the workers of the institution, where a special questionnaire was designed based on the approved study plan, and after its arbitration it was distributed to all 161 workers of Algeria Telecom, we were able to retrieve 150 valid questionnaires for analysis, after making sure of their validity and reliability The data was processed using the SPSS statistical program, which was relied on in many relevant statistical tests, to reach a set of results, the most important of which are the following: - The overall average level of delegation of authority and its relationship to career performance was high, indicating that delegation of authority is related to the level of functioning. - The overall average level of effective communication and its relationship with job performance has been high, which indicates that effective communication and information sharing has to do with job performance. - The overall average of the stimulus axis and its relationship to job performance was high, which indicates that the stimulus has to do with the level of career performance, and in the light of previous findings and analyses of management empowerment dimensions (Delegation of authority, stimulus, effective communication) were all high and positive And so it was concluded that there is a statistically positive correlation between managerial empowerment and functional performance, Meaning that the higher the level of managerial empowerment, the higher the level of functioning of the enterprise's employees s views and perceptions of study variables across their personal and functional characteristics ------------------------------------- ملخص الدراسة: تهدف هذه الدراسة إلى تحليل العلاقة بين التمكين الإداري والأداء الوظيفي لدى العاملين في شركة اتصالات الجزائر، بولاية سوق أهراس. ويتمثل السؤال الرئيسي في الآتي: ما طبيعة العلاقة بين التمكين الإداري والأداء الوظيفي؟ وللتحقق من ذلك، وباستخدام المنهج الوصفي، أجرينا مسحًا شاملًا لجميع العاملين في المؤسسة، حيث صُمم استبيان خاص بناءً على خطة الدراسة المعتمدة، وبعد تحكيمه وتوزيعه على جميع العاملين في شركة اتصالات الجزائر والبالغ عددهم 161 عاملًا، تمكنا من استرجاع 150 استبيانًا صالحًا للتحليل، بعد التأكد من صحتها وثباتها. وتمت معالجة البيانات باستخدام برنامج SPSS الإحصائي، والذي تم الاعتماد عليه في العديد من الاختبارات الإحصائية ذات الصلة، للوصول إلى مجموعة من النتائج، من أهمها: - جاء المتوسط ​​العام لمستوى تفويض السلطة وعلاقته بالأداء الوظيفي مرتفعًا، مما يدل على أن تفويض السلطة مرتبط بمستوى الأداء. - كان المتوسط ​​العام لمستوى التواصل الفعال وعلاقته بالأداء الوظيفي مرتفعًا، مما يدل على أن التواصل الفعال وتبادل المعلومات له علاقة بالأداء الوظيفي. كان المتوسط ​​العام لمحور التحفيز وعلاقته بالأداء الوظيفي مرتفعًا، مما يدل على أن التحفيز له علاقة بمستوى الأداء الوظيفي، وفي ضوء النتائج والتحليلات السابقة لأبعاد التمكين الإداري (تفويض السلطة، التحفيز، التواصل الفعال) كانت جميعها مرتفعة وإيجابية. وبناءً على ذلك، تم التوصل إلى وجود علاقة ارتباطية موجبة إحصائيًا بين التمكين الإداري والأداء الوظيفي، أي أنه كلما ارتفع مستوى التمكين الإداري، ارتفع مستوى أداء موظفي المنشأة لمتغيرات الدراسة من خلال خصائصهم الشخصية والوظيفية.
Keywords: التمكين الإداري، الأداء الوظيفي